THE ROLE OF COMMISSION AS A DRIVING FACTOR FOR EMPLOYEE MOTIVATION IN SEEKING CUSTOMERS TO ACHIEVE CLOSING AT PT AGRODANA FUTURES - I Made Pratama Sujana Putra; Bowo Santoso (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
This study aims to directly understand how the role of commission as a motivating factor for employees in finding customers to achieve closing at PT. Agrodana Futures. The commission system implemented by the company is not only given once at the time of closing or opening a customer account but is also given repeatedly every time a customer makes a transaction activity. The method used in this study is descriptive qualitative with data collection techniques through direct observation and documentation during the internship period. The results of the study indicate that the commission system provides a significant boost to employee enthusiasm and work motivation, especially in prospecting and follow-up activities for prospective customers. Employees who have active customers and receive regular commissions tend to show more stable performance and high initiative in maintaining relationships with customers. The commission also creates a competitive and collaborative work atmosphere through activities such as morning briefings and monthly top commission distribution. However, challenges remain, such as customers who do not understand the risks and mechanisms in futures trading and require an educational approach and personal communication from employees. Therefore, company support in the form of training and provision of educational materials is needed to maintain the sustainability of the commission system and customer loyalty.